Building back better? Taking stock of the post-earthquake mental health and psychosocial response in Nepal - Chase, Liana E. (Int J Ment Health Syst, 2018)
BACKGROUND: The World Health Organization’s ‘building back better’ approach advocates capitalizing on the resources and political will elicited by disasters to strengthen national mental health systems. This study explores the contributions of the response to the 2015 earthquake in Nepal to sustainable mental health system reform. METHODS: We systematically reviewed grey literature on the mental health and psychosocial response to the earthquake obtained through online information-sharing platforms and response coordinators (168 documents) to extract data on response stakeholders and activities. More detailed data on activity outcomes were solicited from organizations identified as most active in the response. To triangulate and extend findings, we held a focus group discussion with key governmental and non-governmental stakeholders in mental health system development in Nepal (n = 10). Discussion content was recorded, transcribed, and subjected to thematic analysis. RESULTS: While detailed documentation of response activities was limited, available data combined with stakeholders’ accounts suggest that the post-earthquake response accelerated progress towards national mental health system building in the areas of governance, financing, human resources, information and research, service delivery, and medications. Key achievements in the post-earthquake context include training of primary health care service providers in affected districts using mhGAP and training of new psychosocial workers; appointment of mental health focal points in the government and World Health Organization Country Office; the addition of new psychotropic drugs to the government’s free drugs list; development of a community mental health care package and training curricula for different cadres of health workers; and the revision of mental health plans, policy, and financing mechanisms. Concerns remain that government ownership and financing will be insufficient to sustain services in affected districts and scale them up to non-affected districts. CONCLUSIONS: Building back better has been achieved to varying extents in different districts and at different levels of the mental health system. Non-governmental organizations and the World Health Organization Country Office must continue to support the government to ensure that recent advances maximally contribute to realising the vision of a national mental health care system in Nepal.